Comparative evaluation of two carbohydrate force fields for modelling polysaccharide conformation - Lazar, Ryan (Department of Computer Science, 2023)
Modern carbohydrate simulation models have reached a level of maturity whereby their accuracy is often assumed. However, concerning differences have been reported when comparing the conformational predictions of rhamnose-rich polysaccharides between GLYCAM06 and other widely used carbohydrate force fields. This thesis investigates the scope and origin of these differences. We compare Molecular Dynamics simulations of strategically selected saccharide chains, with both the GLYCAM06 and CHARMM36 carbohydrate force fields. We find significant differences in the conformational predictions of the two force fields. More specifically, collapsed, globular conformations occur in the GLYCAM06 simulations, but are absent in the equivalent CHARMM36 results. The collapsing phenomenon is brought about by a gradual folding process, facilitated by instabilities in the GLYCAM06 a-L-Rha(1®X)-a-L-Rha glycosidic linkage that are stabilised by strong intramolecular interactions. The reduced consideration for repulsive Coulombic forces in GLYCAM06, originating from a collective lack of partial aliphatic hydrogen charges, is likely the principle factor behind these differences. This work suggests critical areas for refinement in GLYCAM06 that will be required for the force field to accurately model rhamnose-rich polysaccharides. The insights gained in this work have the potential to assist in the development of more accurate force fields for modelling carbohydrates.